Household Hazardous Waste Management - Mmereki, Daniel (IntechOpen, 2017)
Rapid global urbanization and increases in living standards in recent decades have led to changes in the household hazardous waste (HHW) generation characteristics due to increases in buying power and easier access to products that are convenient but not always safe. In recent years, the amount of diversified hazardous materials and/or potentially hazardous materials, such as cleaning products, medicines, personal care products, packaging and container products, phthalates, and antibacterial agents, poses a serious threat to the environment and public health. As a result developed countries have adopted well-functioning policy measures and innovative technologies to deal with HHW. On the other hand, developing countries have weak institutional structures and poor policy performance and have adopted ad hoc approaches to manage HHW. The book contains five chapters covering topics of household hazardous waste management and exposure assessment. This book will be useful to many research scientists, solid and hazardous waste managers, administrators, librarians, and students in the scope of development in solid and hazardous waste management program including sources of household hazardous waste, exposure assessment, and government policies on waste generation and treatment and processing of HHW.